2006
DOI: 10.1177/153303460600500102
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Gold Marker Implants and High-Frequency Jet Ventilation for Stereotactic, Single-Dose Irradiation of Liver Tumors

Abstract: With reference to radiosurgery of the liver, we describe techniques designed to solve the methodological problem of striking targets subject to respiratory motion with the necessary precision. Implanting a gold marker in the vicinity of the liver tumor was the first step in ensuring the reproducibility of the isocenter's position. An 18-karat gold rod measuring 1.9 × 3 mm was implanted approximately 2 cm from the edge of the tumor as this was displayed in the spiral, thin-slice CT with contrast media. Both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…Use of HFJV was primarily introduced to achieve immobilization for accurate targeting in single-fraction stereotactic radiotherapy of lung tumors, because pinpointing the target was of crucial significance, as it had to be eradicated with a single shot. As already reported (3,16,17), and in accordance with our experience, the abdominal compression device integrated into the stereotactic frame often limits tumor movement inadequately. In contrast to non-HFJV SBRT patient set-up uncertainties under general anesthesia and HFJV have not been observed.…”
Section: Hfjv-ct Gtvsupporting
confidence: 89%
See 1 more Smart Citation
“…Use of HFJV was primarily introduced to achieve immobilization for accurate targeting in single-fraction stereotactic radiotherapy of lung tumors, because pinpointing the target was of crucial significance, as it had to be eradicated with a single shot. As already reported (3,16,17), and in accordance with our experience, the abdominal compression device integrated into the stereotactic frame often limits tumor movement inadequately. In contrast to non-HFJV SBRT patient set-up uncertainties under general anesthesia and HFJV have not been observed.…”
Section: Hfjv-ct Gtvsupporting
confidence: 89%
“…This method has already been tested with a preclinical animal study in SBRT for the liver [21] and has been established as the best procedure for single-fraction SBRT of metastases of the liver in our clinic [16]. Its feasibility in SBRT for the lungs was uncertain at the outset, but our standardized procedure has proved effective for all of the patients.…”
Section: Hfjv-ct Gtvmentioning
confidence: 95%
“…The reports we have cited consider the application of HFJV to radiation therapy, percutaneous thermal ablation, or extracorporeal shock wave lithotripsy. To summarize, Fritz et al [3], working with radiotherapy, showed that HFJV enabled liver motion to be minimized to 3 mm, in agreement with Denys et al experience. In the field of percutaneous ablation, the only series we found in literature was a retrospective observational study published in 2011 in which nine patients with hepatic or renal lesions were treated under HFJV [4].…”
supporting
confidence: 59%
“…In a retrospective comparison of HFJV to spontaneous ventilation in patients undergoing extracorporeal shock wave lithotripsy, Cormack et al [4] found a significant decrease in the number of shocks necessary to obtain stone ablation. Fritz and colleagues [5] showed, in 10 patients, that HFJV produced reliable immobilization of gold markers placed stereotactically in the liver during tumor biopsy. LaraGuerra et al [6] showed that conditions for CT-guided excision of lung nodules in ex vivo lungs with HFJV approached those of inflation to total lung capacity or total lung deflation.…”
Section: Discussionmentioning
confidence: 98%